1994
DOI: 10.1093/clinids/18.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amphotericin B During Pregnancy: Case Report and Review

Abstract: Unlike the situation with many antimicrobial agents, there is limited experience with the use of amphotericin B during pregnancy. Although reports of fungal infections during pregnancy have been published, few describe fungemia with either Candida or Torulopsis species. We present a case of fungemia due to Torulopsis glabrata that occurred during pregnancy and that was treated with amphotericin B. Drug concentrations were measured in placental tissue, cord serum, and infant serum at delivery. Although the last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 17 publications
0
19
0
2
Order By: Relevance
“…Since the introduction of the azoles, especially the bisazole fluconazole, has broadened the spectrum of systemic antimycotic therapy, the exclusive use of amphotericin B during pregnancy in life-threatening fungal diseases is disputable. As recently reported, amphotericin B has been used in 29 pregnant women so far [17]. Nephrotoxicity led to death in two of these patients [28].…”
Section: Literature Review and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Since the introduction of the azoles, especially the bisazole fluconazole, has broadened the spectrum of systemic antimycotic therapy, the exclusive use of amphotericin B during pregnancy in life-threatening fungal diseases is disputable. As recently reported, amphotericin B has been used in 29 pregnant women so far [17]. Nephrotoxicity led to death in two of these patients [28].…”
Section: Literature Review and Discussionmentioning
confidence: 81%
“…In the recent literature there are only a few reports on fungemia during pregnancy [16,17], and thus the mother's and the fetus's risk of inner organ involvement and mortality rates due to Candida septicemia still remain unknown. Gestational colonization of the mucosal sites with C. albicans, however, is well documented and appears to be not only a commensal but also an infectious agent, at least in the vagina of pregnant women as it accounts for 80% of fungal infections of the mucous membranes [18].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Although the FDA pregnancy category provides guidance regarding a drug's potential fetal risks, limitations such as a lack of a specifi c toxic dose or predisposing pregnancy trimester complicate its application 22 . Amphotericin B can cross the placenta and reach low concentrations in the amniotic fl uid 23 , but its safety in pregnant women was established in the treatment of systemic mycoses 18 . No studies were found assessing the effectiveness of amphotericin B in ATL treatment.…”
Section: Resultsmentioning
confidence: 99%
“…6 Although the exact mode of elimination of amphotericin B remains to be clarified, the researchers suggested that the agent accumulates in tissues that then acts as a reservoir from which amphotericin B is slowly released back into circulation.…”
Section: Discussionmentioning
confidence: 99%